Carbothermal synthesis of LiVPO4F and its structural change in a broad potential range observed by in-situ X-ray diffraction. Issue 9 (November 2015) - Li, Peng; Wang, Pengfei; Yu, Haoxiang; Lin, Xiaoting; Shao, Lianyi; Shui, Miao; Long, Nengbing; Shu, Jie
Abstract: In this work, a novel lithium storage material LiVPO4 F is synthesized and reported for advanced lithium-ion batteries. By using the carbothermal reduction method, LiVPO4 F is prepared with VPO4 as the intermediate precursor. The as-prepared LiVPO4 F particles reveal an average particle size of 400 nm and are surrounded by conductive carbon black particles with size of 30–50 nm. Over-discharge tests show that LiVPO4 F has good reversibility with the discharge/charge capacities of 556.0/391.4 mAh g −1 in the potential range of 0.0–4.7 V. In-situ and ex-situ observations prove that the structural evolution of VPO4 F during an over-discharge process to 0.0 V is associated with the phase transformation of VPO4 F→LiVPO4 F→Li2 VPO4 F→Li3 VPO4 F. The corresponding recharge process is a quasi-reversible reaction, which is related to the delithiation process of Li3 VPO4 F→Li2 VPO4 F→LiVPO4 F→Li x VPO4 F→VPO4 F. All these results indicate that LiVPO4 F has good over-discharge resistant ability as cathode material for lithium-ion batteries.